Particle emissions from mobile sources: Discussion of ultrafine particle emissions and definition. (January 2022) - Kittelson, David; Khalek, Imad; McDonald, Joseph; Stevens, Jeffrey; Giannelli, Robert
Abstract: There is no universally agreed upon definition for ultrafine particles (UFP). Commonly used definitions for UFP are either particle number below 100 nm or total particle number, but without an agreed upon lower cut point. For example, a lower cut point of 3 nm compared to 10 nm could result in a substantially higher count. Another definition for UFP is total particle mass but without a commonly agreed upon aerodynamic diameter upper cut point, e.g., below 100 nm, 200 nm, 300 nm, etc. Yet another definition is lung deposited surface area weighted by lung deposition fraction, found mainly in the particle mobility diameter range from 20 to 400 nm. It is clear from these definitions that there are inconsistencies in the way UFP is used and defined in the literature. Sometimes these metrics are well correlated, sometimes not. In this paper we suggest three exposure metrics: UFP-N, UFP-M, and UFP-S, that we believe will add clarity. These metrics represent total number, mass, and surface area below 500 nm, respectively. For surface area and mass, the 500 nm cut point can be either aerodynamic or mobility diameter depending upon measurement methodology. For all metrics, this cut point captures nearly all of the primary particle emissions from mobile sources. Furthermore, UFP-N would include a lower cut point of 3–6 nm and would not require an upper size cut point because there is very little particle number above 500 nm or even above 100 nm. Thus, our definition of UFP-N is consistent with the current definition of ultrafine number except for, importantly, the specification of a lower cut point. These exposure metrics can help facilitate consistency in the characterization of both short- and long-term UFP ambient exposures and associated health effects in epidemiological studies. Highlights: Highest human exposure to Ultrafine particles (UFP) is on-road and near-road. PM2.5 and UFP epidemiological impacts at present are indistinguishable. UFP are ill-defined in the literature, typically number based and do not capture the surface area and mass metrics. We recommend UFP be defined as particles between 500 nm and approximately 3 nm in diameter. Most near roadway mobile source emissions of particle number, surface area and mass, are captured by the new UFP definition.